Arm assembly : internals & reverse engineering - Markstedter, Maria (John Wiley & Sons, Inc., 2023)
Finding and mitigating security vulnerabilities in Arm devices is the next critical internet security frontier—Arm processors are already in use by more than 90% of all mobile devices, billions of Internet of Things (IoT) devices, and a growing number of current laptops from companies including Microsoft, Lenovo, and Apple. Written by a leading expert on Arm security, Blue Fox: Arm Assembly Internals and Reverse Engineering introduces readers to modern Armv8-A instruction sets and the process of reverse-engineering Arm binaries for security research and defensive purposes.